Pemberdayaan Perempuan Melalui Kegiatan Agroprocessing Komoditas Pertanian untuk Menunjang Kawasan Agribisnis di Kecamatan Pasirwangi Kabupaten Garut, Program Pengabdian Masyarakat dengan Skim Ipteks Bagi Masyarakat (IbM) - Okke Rosmaladewi; Ibrahim Danuwikarsa; Rubi Robana; Lilis Irmawatie; Ida Adviany; Erry Mustariani (LPPM UNINUS, 2011)
Agroprocessing of agricultural commodities is an undertaking a value-added products into augmented, thereby increasing farm incomes which is finally expected could improve farmer families welfare. Community Service Program by Science and Technology scheme for community (IBM) in the form of women empowerment through activities in agroprocessing of agricultural commodities supporting agribusiness area in Pasirwangi district, Garut regency had been conducted with participants from the mothers’cadres in Empowerment Family Welfare (PKK) of the same place. The implementation of community empowerment model in this program synergizes three elements: Academician, Business perpetrator and Government that used to do community activities in the same place with each programs. This program has successfully trained agroprocessing of agricultural commodities skills footed up to 36 participants (all participants is women) representing 12 villages in Pasirwangi districts and set as Local Facilitators and has spread the knowledge to people in their villages. As a medium for increasing economic of denizens on agroprocessing activity formed the Joint Business Group (KUBE) in Talaga and Padaawas village, while in Sirnajaya village enabled cooperative society that already exist